Publisher Correction to: Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)

Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)
Urban populations face increasing vulnerability to extreme heat events, particularly in rapidly urbanising Global South cities where environmental exposure intersects with socioeconomic inequality and limited healthcare access. This study quantifies heat vulnerability across Johannesburg, South Africa, by integrating high-resolution environmental data with socio-economic and health metrics across 135 urban wards. We examine how historical urban development patterns influence contemporary vulnerability distributions using principal component analysis and spatial statistics. Environmental indicators (Land Surface Temperature (LST), vegetation indices, and thermal field variance) were combined with socioeconomic and health variables (including indicators on crowded dwellings and healthcare access, self-reporting of chronic diseases) in a comprehensive vulnerability assessment. Principal Component Analysis revealed three primary dimensions explaining 56.6% (95% CI: 52.4–60.8%) of the total variance: urban heat exposure (31.5%), health status (12.8%), and socio-economic conditions (12.3%). Built-up areas showed weak but significant correlations with heat indices (ρ = 0.28, p < 0.01), while higher poverty levels demonstrated moderate positive correlations with LST (ρ = 0.41, p < 0.001). The spatial analysis identified significant clustering of vulnerability (Global Moran's I = 0.42, p < 0.001), with distinct high-vulnerability clusters in historically disadvantaged areas. Alexandra Township showed the highest vulnerability(HVI score: 0.87, LST: 29.8 °C ± 0.4 °C, NDVI: 0.08 ± 0.02), with factors characterising the high vulnerability in that area including limited healthcare access and extreme heat exposure. Northern suburbs formed a significant low-vulnerability cluster (Mean HVI = 0.23 ± 0.07, p < 0.001), benefiting from greater vegetation coverage and better healthcare access. These findings demonstrate how historical planning decisions continue to shape contemporary environmental health risks, with vulnerability concentrated in areas of limited healthcare access and high extreme heat exposure. Results suggest the need for targeted interventions that address both environmental and social dimensions of heat vulnerability, particularly focusing on expanding healthcare access in identified hotspots and implementing community-scale green infrastructure in high-risk areas. This study provides an evidence-based framework for prioritising heat-resilience initiatives in rapidly urbanising Global South cities while highlighting the importance of addressing historical inequities in urban adaptation planning.

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

Lake shape and the characteristics of migration behavior modify Atlantic salmon smolt migration success through lakes - Matthew Newton; Joseph McCallum; Hannele M. Honkanen; Alastair Stephen; Jessie M. Lilly; Danielle L. Orrell; Amy Green; Louise Chavarie; Jessica R. Rodger; Colin E. Adams (Journal of Fish Biology, 2025)
Migration is a high‐risk behavior. For the Atlantic salmon, Salmo salar , migrating from its river nursery area to marine feeding grounds, the magnitude of risk varies with habitat type. Passage through lakes, in particular, is associated with low rates of migration success. Downstream migrating salmon smolts are rheotactic when migrating in rivers, but lakes typically provide poorer directional currents for migrating salmon. In this study we tested if, in the absence of clear navigational cues in lakes, Atlantic salmon smolts switch to a random search strategy to find the outflowing river. We constructed random search simulations to test if lake basin shape has an effect on migration success. We also compared simulated migration characteristics with migrations of salmon smolts through five real lakes for which there are telemetry data for migrating salmon. Correlated random walk simulations showed that a random search strategy could be successful for all lake shapes tested but was more successful in curved (round and elliptical) than rectangular basin shapes. Rectangular basins with the migration start and stop points at the ends of the lake had a higher success than those where these points were perpendicular to the axis of the lake. In general, a random walk model predicted the migration success rate of fish tracked through real lakes. However, for two lakes the simulated migration success exceeded that of actual success, suggesting that fish passing through these lakes were not adopting a random search strategy. We speculate that this is the result of either conflicting navigational cues which inhibit smolts from finding the lake outlet or that they temporarily suspend migration (e.g., to feed). Modelling predicted that for small lakes, directional swimming in short steps (ca. 100 m) followed by turns with very low variation from the direction of travel resulted in the highest migration success. For larger lakes, longer step lengths but also with low turn variation (simulated turning angle drawn from distributions of standard deviation 2 ° and 5 ° around a mean of 0 ° ) resulted in the highest migration success. We conclude that navigation in downstream migrating salmon smolts switches from rheotaxis in rivers to a random search tactic in lakes except where residual flow cues in some lakes prevent this, at times resulting in suboptimal navigation outcomes.

Extended one-generation reproductive toxicity study of food-grade titanium dioxide E171 with emphasis on reproductive and endocrine endpoints - Rodger V. Battersby; Janine Adam; Amy L. Williams; John M. DeSesso (Reproductive Toxicology, 2024)

Novel Small-Molecule Improves Mitochondrial Function and Mitophagy in a Complex III Deficiency Model - Lucía Fernández-del-Rio; Andrea Eastes; Matheus P. Oliveira; Karel Erion; David R.F. Pacheco; Jasmine Garza; Matthew Dugan; Sophie Kantor; Iman Gauhar; Philip Ma; Jonathan Wanagat; Kathleen Rodgers; et al. (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Beat-to-beat blood pressure variability, hippocampal atrophy, and memory impairment in older adults - Trevor Lohman; Isabel Sible; Allison C. Engstrom; Arunima Kapoor; Fatemah Shenasa; Elizabeth Head; Lorena Sordo; John Paul M. Alitin; Aimee Gaubert; Amy Nguyen; Kathleen E. Rodgers; David Bradford; et al. (GeroScience, 2024)
Visit-to-visit blood pressure variability (BPV) predicts age-related hippocampal atrophy, neurodegeneration, and memory decline in older adults. Beat-to-beat BPV may represent a more reliable and efficient tool for prospective risk assessment, but it is unknown whether beat-to-beat BPV is similarly associated with hippocampal neurodegeneration, or with plasma markers of neuroaxonal/neuroglial injury. Independently living older adults without a history of dementia, stroke, or other major neurological disorders were recruited from the community ( N = 104; age = 69.5 ± 6.7 (range 55–89); 63% female). Participants underwent continuous blood pressure monitoring, brain MRI, venipuncture, and cognitive testing over two visits. Hippocampal volumes, plasma neurofilament light, and glial fibrillary acidic protein levels were assessed. Beat-to-beat BPV was quantified as systolic blood pressure average real variability during 7-min of supine continuous blood pressure monitoring. The cross-sectional relationship between beat-to-beat BPV and hippocampal volumes, cognitive domain measures, and plasma biomarkers was assessed using multiple linear regression with adjustment for demographic covariates, vascular risk factors, and average systolic blood pressure. Elevated beat-to-beat BPV was associated with decreased left hippocampal volume ( P = .008), increased plasma concentration of glial fibrillary acidic protein ( P = .006), and decreased memory composite score ( P = .02), independent of age, sex, average systolic blood pressure, total intracranial volume, and vascular risk factor burden. In summary, beat-to-beat BPV is independently associated with decreased left hippocampal volume, increased neuroglial injury, and worse memory ability. Findings are consistent with prior studies examining visit-to-visit BPV and suggest beat-to-beat BPV may be a useful marker of hemodynamic brain injury in older adults.

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Does reward regulate habitual consumption behaviour? - Amy Rodger; Lawrence W. Barsalou; Esther K. Papies (Appetite, 2023)

Can a simple plan change a complex behavior? Implementation intentions in the context of water drinking - Amy Rodger; Ariel Vezevicius; Esther K. Papies (Appetite, 2023)

Threats posed to conservation by media misinformation - Adam G. Hart; Rosie Cooney; Amy Dickman; Darragh Hare; Charles Jonga; Paul K. Johnson; Maxi Pia Louis; Rodgers Lubilo; Dilys Roe; Catherine Semcer; Keith Somerville (Conservation Biology, 2020)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Endogenous Sex Steroids Dampen Neuroinflammation and Improve Outcome of Traumatic Brain Injury in Mice - Amy C. Clevenger; Hoon Kim; Ernesto Salcedo; Joan C. Yonchek; Krista M. Rodgers; James E. Orfila; Robert M. Dietz; Nidia Quillinan; Richard J. Traystman; Paco S. Herson (Journal of Molecular Neuroscience, 2018)